METABOLIC FATE OF DIETARY NON-PROTEIN NITROGEN IN HETEROPNEUSTES FOSSILIS (BLOCH) - Mukhopadhyay, Pratap K; Dehadrai, Padmakar V (Indian Journal of Fisheries, 2011)
The metabolic fate of non-protein nitrogen (NPN) from urea as component of supplementary diet was investigated in the catfish Heteropneustes fossilis. Urea substitution (3% by weight of food), replacing approximately one-fifth of dietary protein (8.6 g protein s 1.38 g N r ) , registered a better growth performance. An increased intestinal urease activity could be recorded from urea-diet treatment. The activities of liver arginase, alanine aminotransferase and aspartate aminotransferase together with the level of blood urea were also studied in response to NPN-diet treatment. All these indicated possibilities of NPN assimilation. Again, the bioconversion of dietary NPN to tissue protein was ascertained by mass spectrometric studies. No gross change in food value was observed when the fish was fed on the NPN diet over a rather prolonged period